Studying Political Economies of Communication in the Twenty-First Century. Issue 1 (3rd April 2018) - Wasko, Janet
Abstract : This article celebrates the anniversary of Javost—The Public by briefly noting the continuing growth and contribution of the critical study of political economies of media and communication. The discussion includes some of the variations and critiques, of this approach, as well as current trends and directions. The main argument is that critical approaches to understand the political economy of media/communication are still valuable and needed to fully understand issues relating to democracy and the public sphere.